Concreteness and Contraception: Beauvoir’s Second Sex and the Affordable Care Act - Kirkland, Katie Lane (Stance: an international undergraduate philosophy journal, 2015)
In this paper, I analyze Simone de Beauvoir’s goals for women expressed in The Second Sex and compare these goals to the opportunities created by the Affordable Care Act’s contraceptive mandate. Though the contraceptive mandate advances Beauvoir’s goal of concrete equality by supporting economic independence and recognizing women’s sexual freedom, there are social and political limitations to these advancements.